ANALISIS KONDISI BANGUNAN DAN FASILITAS SANITASI TEMPAT PENGELOLAAN MAKANAN (TPM) DI KECAMATAN CILEDUG, TANGERANG TAHUN 2020 - Namira Prisar Kinanti, (2021)
The incidence rate of diarrhea in 2017 in Ciledug was 2.669 cases.and in 2018 increased to 3.164 cases. One of the factors that can increase diarrhea cases is sanitation, not only at home but also in the food management place because there're highly risk that can spread disease and food poisoning. The purpose of this study was analyzing building condition and sanitation facilities in the food management place in Ciledug, Tangerang in 2020. Design of this study was observational. Population of this study were 210 food management places in Ciledug, Tangerang and the samples of this study were 138 food management places. This study used simple random sampling technique for sampling. This study used checklist as the instrument. Data were analyzed by univariate analysis. The results show that yard (100,0%), construction (98,6%), floor (94,2%), ceiling (74,6%), wall (68,8%), lighting (94,9%), ventilation (92,0%), clean water (89,1%), hand-washing facilities and toilet (81,9%), and kitchen (74,6%) meet the standard but door and window (61,6%) and dump (60,1%) didn't meet the standard. Recommendation for the owner of food management places are to set insect repellent equipment, to close the door, to throw away unuseful things, to replace the trash bin with the close one.